Making sense of reading : - Maingay, Susan (Harrap, 1983)
Making sense of reading is an introduction to reading skills for students of intermediate level. Each of the ten units contains authentic British or American texts and accompanying sets of exercises and activities which are designed to develop and improve the basic skills necessary for efficient reading.